2013
DOI: 10.26719/2013.19.7.644
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of diabetes among type 2 diabetes patients attending a primary health care clinic in Sri Lanka

Abstract: Patients' knowledge about their illness is considered important in controlling diabetes and preventing complications. A descriptive, cross-sectional study was conducted among patients attending the diabetes clinic of a primary care level hospital in Moratuwa, Sri Lanka. During a 1-month period in 2009 all consenting patients diagnosed with type 2 diabetes who had been attending the clinic for more than 3 months were included in the study. Using an interviewer administered, structured questionnaire 150 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
22
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 13 publications
(10 reference statements)
8
22
0
4
Order By: Relevance
“…A previous study, conducted in Pakistan, to assess the knowledge of diabetes among patients with diabetes revealed that only 13.6% of the participants had a good knowledge about diabetes (14). A similar study conducted at Moratuwa, Sri Lanka, showed that more than 90% of the participants were unable to recognize hyperglycaemic and hypoglycaemic symptoms, 42% of the participants didn't know the target blood glucose level and more than 50% of the participants didn't believe annual follow-ups were needed to manage their condition (15). 90% of the participants in this study were female and they lived in a specific geographical area and generalizability of the study findings was debatable.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…A previous study, conducted in Pakistan, to assess the knowledge of diabetes among patients with diabetes revealed that only 13.6% of the participants had a good knowledge about diabetes (14). A similar study conducted at Moratuwa, Sri Lanka, showed that more than 90% of the participants were unable to recognize hyperglycaemic and hypoglycaemic symptoms, 42% of the participants didn't know the target blood glucose level and more than 50% of the participants didn't believe annual follow-ups were needed to manage their condition (15). 90% of the participants in this study were female and they lived in a specific geographical area and generalizability of the study findings was debatable.…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies done in Sri Lanka (15), India (18) and Singapore (17) have demonstrated that 44%, 62% and 25% of the patients in respective countries believed that diabetes is curable 8 . This study also demonstrated a similar percentage of patients (47%) who believes that diabetes can be cured and take treatment hoping for a cure.…”
Section: Referencesmentioning
confidence: 99%
“…Although the majority of patients are aware of the chronic complications of diabetes, a reasonable percentage of patients were unaware of the symptoms of hypoglycaemia (64%). The previous studies done in Sri Lanka also have demonstrated that the majority of (90%) patients were unaware of the symptoms of hyperglycemia or hypoglycemia and only 20.7% patients were knowledgeable about symptoms of hypoglycemia (12,17,22,29). A similar study done in India has also shown that only about 51.5% of the patients were aware of the symptoms of hypoglyaemia (28).…”
Section: Knowledge Score On Complications Of Diabetesmentioning
confidence: 99%
“…According to a statement by the American association of clinical Endocrinologists, the cause of compli--cations in both acute and chronic DM is either a lack of understanding with regard to the long and short-term regulation of blood glucose or the refusal of the patients to control the blood glucose levels (21). A study done by Perera et al in 2013 has demonstrated that 90.0% of the study participants knew that DM produces chronic complications (22). In contrast, the study by Mohan et al (2005) in Chennai (India) found that only 40.6% of self-reported diabetic subjects knew that DM could cause complications (23).…”
Section: Knowledge Score On Complications Of Diabetesmentioning
confidence: 99%
“…Recent evidence of studies from Perera, et al and Jayawardena, et al reported the limited patients' knowledge on the management of their disease in Sri Lanka which underlines an urgent need of setting an effective culturally sensitive and appropriate education program on lifestyle modification. However, 'Chronic care models have extensively practiced for self-management programs, but to our knowledge, no patient education studies based on 'PITS model' (Pathophysiology, Indications, Treatment and Specifics) has been practiced in Sri Lanka [10][11][12]. The PITS model is a logical, organised universal teaching model that presents information which enhances the receiver's ability to recall information [13,14].…”
Section: Introductionmentioning
confidence: 99%